Urban realities for displaced young women and girls - Tyler, D; Schmeidl, S (Refugee Studies Centre, University of Oxford, 2014)
Growing numbers of IDPs live in informal settlements in major Afghan urban centres but the ways in which displaced young women and girls are vulnerable in such settings are not well enough understood or addressed